2021
DOI: 10.3390/app11167667
|View full text |Cite
|
Sign up to set email alerts
|

Shear Resistance Assessment of the Y-Type Perfobond Rib Shear Connector under Repeated Loadings

Abstract: The steel–concrete composite structures consist of two different material parts, which are connected with reliable shear connectors to enable the combined action of the steel and concrete members. The shear connectors may experience either one-directional repeated cyclic loadings or fully reversed cyclic loadings depending on the structural functions and acting loadings. It is essential for structural engineers to estimate the residual shear strength of the shear connectors after action of repeated loads. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several scholars, including Vianna, Li, Zheng, Lin and Wang et al, analyzed the damage mode of the connector as well as the load–slip relationship by controlling each influencing parameter’s variable based on push-out tests and numerical simulations [ 3 , 26 , 27 , 28 , 29 ], while studying the shear resistance of PBL connectors as well. Suzuki and Kim et al considered the state of the shear connector subjected to repeated loading in the actual operation and studied it through extensive push-out tests and numerical simulations, and found that the PBL connector was superior to the conventional pinned connector under this loading condition, and proposed their design of residual shear strength discount factors and design equations for the shear strength under cyclic loading [ 30 , 31 , 32 ]. Through the study of PBL connectors by many scholars, it can be found that the calculation method of shear capacity is a key point for evaluating the shear performance of PBL connectors, and the calculation method of shear capacity can be deduced by the combination of numerical simulations and parameter analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars, including Vianna, Li, Zheng, Lin and Wang et al, analyzed the damage mode of the connector as well as the load–slip relationship by controlling each influencing parameter’s variable based on push-out tests and numerical simulations [ 3 , 26 , 27 , 28 , 29 ], while studying the shear resistance of PBL connectors as well. Suzuki and Kim et al considered the state of the shear connector subjected to repeated loading in the actual operation and studied it through extensive push-out tests and numerical simulations, and found that the PBL connector was superior to the conventional pinned connector under this loading condition, and proposed their design of residual shear strength discount factors and design equations for the shear strength under cyclic loading [ 30 , 31 , 32 ]. Through the study of PBL connectors by many scholars, it can be found that the calculation method of shear capacity is a key point for evaluating the shear performance of PBL connectors, and the calculation method of shear capacity can be deduced by the combination of numerical simulations and parameter analyses.…”
Section: Introductionmentioning
confidence: 99%